BANK COMPETITION AND FINANCIAL STABILITY IN NIGERIA - Mayowa Ebenezer Ariyibi; Taofeek Osidero Agbatogun; Kenny Ade Soyemi (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: The study examined the impact of bank competition on the financial stability of selected deposit money banks in Nigeria. The study employed panel data (secondary data) that was collected from 2019 to 2023 (both years inclusive).